(η(6)-p-cymene)Ru(H2O)3](2+) binding capability of aminohydroxamates - A solution and solid state study - Parajdi-Losonczi, Péter László; Bényei, Attila Csaba; Kováts, Éva; Timári, István; Muchova, Tereza Radosova; Novohradsky, Vojtech; Kasparkova, Jana; Buglyó, Péter (Journal of inorganic biochemistry, 2016)
Complex forming capabilities of [(η(6)-p-cymene)Ru(H2O)3](2+) with aminohydroxamates (2-amino-N-hydroxyacetamide (α-alahaH), 3-amino-N-hydroxypropanamide (β-alahaH) and 4-amino-N-hydroxybutanamide (γ-abhaH)) having the primary amino group in different chelatable position to the hydroxamic function were studied by pH-potentiometry, NMR and MS methods. Formation of stable [O,O] and mixed [O,O][N,N] chelated mono- and dinuclear species is detected in partially slow with α-alahaH and β-alahaH or in fast processes with γ-abhaH and the formation constants of the complexes present in aqueous solution are reported. Synthesis, spectral (NMR, IR) and ESI mass spectrometric characterization of novel dinuclear α-alaninehydroximato complexes containing the half-sandwich type Ru(II) core is described. The crystal and molecular structure of [{(η(6)-p-cymene)Ru}2(μ(2)-α-alahaH-1)(H2O)Br]Br∙H2O (1) and [{(η(6)-p-cymene)Ru}2(μ(2)-α-alahaH-1)(H2O)Cl]BF4∙H2O (2) was determined by single crystal X-ray diffraction method. In the complexes one half-sandwich core is coordinated by a hydroxamate [O,O] chelate while the other one by [Namino,Nhydroxamate] fashion of the bridging ligand. In both cases the remaining coordination sites of one of the Ru cores are taken by a halide ion whiles the other one by a water molecule. Reaction of 2 with 9-methylguanine indicates the N7 coordination of this simple DNA model. Complexes 1 and 2 were tested for their in vitro cytotoxicity using human-derived cancer cell lines (A2780, MCF-7, SKOV-3, HCT-116, HeLa) and showed no anti-proliferative activity in the micromolar concentration range.
Keywords: HeLa Cells; Ruthenium complexes; guanin; Organometallic Compounds; Cell Line, Tumor; GABA; HCT116 buňky; gamma-Aminobutyric Acid; MFC-7 buňky; nádorové buněčné linie; Cymenes; lidé; HeLa buňky; organokovové sloučeniny; HCT116 Cells; Antineoplastic Agents; MCF-7 Cells; protinádorové látky; komplexní sloučeniny; kationty dvojmocné; Hydroxamic Acids; krystalografie rentgenová; cymeny; Anticancer; kyseliny hydroxamové; Coordination Complexes; monoterpeny; Models, Molecular; Aminohydroxamates; molekulární modely; Guanine; Ruthenium; Crystallography, X-Ray; Speciation; X-ray structure; Monoterpenes; Cations, Divalent; ruthenium; Humans